Boosting the performance of an anion exchange membrane by the formation of well-connected ion conducting channels. Issue 22 (15th May 2019) - Li, Yan; Zhang, Jujia; Yang, Hua; Yang, Shanzhong; Lu, Shanfu; Wei, Haibing; Ding, Yunsheng
Abstract : Enlarging the discrepancies between hydrophilic/hydrophobic segments in the chemical structure of an ionomer proved to be an efficient strategy to induce the formation of a microphase-separated morphology of the resulting anion exchange membrane. Abstract : An anion exchange membrane (AEM) with good ion conductivity and high durability is greatly needed in the area of electrochemical energy conversion and storage systems. An AEM with a phase separation morphology has been shown to be an efficient strategy. Here, we randomly tethered a fluorocarbon segment and a tri-quaternary ammonium side chain to the poly(phenylene oxide) (PPO) backbone (PPO-22-3QA8F), aiming to increase the thermodynamic immiscibility between the hydrophobic/hydrophilic units and thereby produce an AEM with better phase separation but suppressed water uptake. With the premise of similar ion contents, two AEMs tethered with tri-quaternary ammonium (PPO-8-3QA) and benzyltrimethylammonium (PPO-22-QA) were synthesized for comparison. Incorporating an additional hydrophobic side chain turned out to be an effective way to drive the membrane's phase separation and the formation of well-connected ion conducting channels. PPO-22-3QA8F exhibited the highest hydroxide conductivity among the three AEMs up to 83 mS cm −1 in Milli-Q water at 90 °C, which is over 2 times higher than that of PPO-8-3QA (39 mS cm −1 ) and PPO-22-QA (27 mS cm −1 ). In addition, PPO-22-3QA8F exhibited a reasonable water uptake of less than 20 wt% at room temperature and excellent alkaline stability in 1 M NaOH at 80 °C for 7 days. As the immersion time was extended to 21 days, the PPO-22-3QA8F membrane was ductile and retained 51% of its original conductivity, while the other two controls were broken to pieces. A H2 /O2 fuel cell prototype was evaluated using the PPO-22-3QA8F membrane as a separator to achieve a peak power density of 102 mW cm −2, which was nearly 3 times higher than that of the PPO-8-3QA membrane (38 mW cm −2 ) under the same operating conditions. Overall, the results of this study provide an efficient strategy to guide the architectural design of high-performance AEMs.